Quo Vadis Inclusive Islamic Education: A Systematic Literature Review (SLR) and Bibliometric Analysis - Muhammad Syafrani Surya Permadi; Rizal Nurdin Ismail; Moch. Chafiid Dhuha; Asep Saepul Hamdani (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study analyzes the development and direction of inclusive Islamic education (Quo Vadis) through a Systematic Literature Review (SLR) and bibliometric analysis of 200 Scopus-indexed articles from 1996 to 2026. Using the PRISMA framework, the study maps publication trends, country and institutional contributions, active authors, and the most productive journals. The results show a significant increase in research since 2018, influenced by the rise of moral decadence and unequal access to education. Indonesia is the largest contributor, confirming the relevance of this theme in the national and global education context. Keyword analysis identified six fundamental principles of inclusive Islamic education: moderation, balance, mutual assistance, equality, justice, and tolerance. This study produced a conceptual framework that emphasizes four key elements of success: educator commitment, curriculum effectiveness, learning outcomes, and parental and environmental support. These findings emphasize the need for a more holistic, contextual, and cross-cultural development of inclusive Islamic education to address today's moral and social challenges.